Faktor Pendukung Keberhasilan Penyelenggaraan Tahfidz Al-Quran di Unit Hai’ah Tahfizh Al-Qur’an Universitas Islam Negeri Maliki Malang - Busra Febriyarni; Nurjannah Nurjannah; Rahmat Iswanto (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Supporting Factors for the Successful Implementation of Tahfidz Al-Quran in the Hai'ah Tahfizh Al-Qur'an Unit, Maliki State Islamic University MalangThis paper aims to provide an overview of the success of the implementation of the Hai'ah Tahfiz al-Quran unit at UIN MALIKI Malang with a phenomenological approach. The method used in this paper is descriptive qualitative to the data obtained from the field. The results obtained that the factors supporting the success of the implementation of tahfizh al-Quran in the Hai'ah Tahfizh Al-Qur'an Unit, Maliki Maulana Malik Ibrahim State Islamic University Malang include the fulfillment of several important elements or elements such as the administrative system, teaching staff, materials, facilities, participants. education, methods, and management. The implementation of tahfizh al-Quran to improve the quality of students needs to be carried out with strong program support at a university as part of management policy and followed by the provision of human resources and supporting facilities